Genetic resistance to foliar anthracnose in sorghum and pathogenic variability in Colletotrichum graminicola - U.S. KUSHWAHA, R.R. DWIVEDl, R. KRISNASWAMY, R.P. THAKUR*, V.P. RAO, S.M. WU, K.V. SUBBARA02, K. MATHUR, H.C. TAILOR; S. INDIRA, R.V. HIREMATH and (Indian Phytopathology, 2007)
Anthracnose, caused by the fungus Colletotrichum graminicola, is a widely prevalent and economically significant disease of sorghum (Sorghum bicolor) in warm and humid regions of ASia, Africa and the America. Disease management through host plant resistance is the most effective option, but the resistance has been often short-lived because of the highly variable pathogen forms. Resistance to foliar anthracnose in sorghum lines and variability in C. graminicola populations were studied through a collaborative International Sorghum Anthracnose Virulence Nursery (ISAVN).The ISAVN, consisting of 15 sorghum lines, were tested at 14 anthracnose hot spots in India, Thailand, Ethiopia, Kenya, Zambia, Nigeria and Mali for 4- 7 years (1992-1998).Foliar anthracnose severity data were recorded at the hard-dough stage of the crop. Anthracnose severity varied significantly among lines, years and locations. The tested sorghum lines exhibited significantly differential resistance. Among the 15 sorghum lines IS 6928, IS 18758, and IS 12467were the most resistant to anthracnose across the environments (locations and years). Analysis of variation in anthracnose severity revealedthat resistance in sorghum lines was variable and dependent on the environment, indicating potential differences in virulence of C. graminicola populations at different locations and over years. Correlation and cluster analyses based on the reactions of tested sorghum lines at different locations suggested that some of the sorghum lines may share certain resistance genes and that the two most resistant lines IS 12467 and IS 6928, may possess different resistance genes. These lines could be ideal sources of resistance for breeding programs.